Upper Gastrointestinal Bleeding Revealing Renogastric Fistula: A Case Report and Literature Review - Yassine Mellagui; Inass Haouli; Jamal Ouachaou; Mohammed Aabdi; Houssam Bkiyar; Brahim Housni (Case Reports in Urology)
A renogastric fistula is a rare complication defined by abnormal communication between the kidney and the stomach. We report the case of a patient admitted to the intensive care unit for hemorrhagic shock following upper gastrointestinal bleeding whose radiological investigations revealed a fistulated renal hematoma in the stomach.